Transformation of Higher Education Policy: A Literature Study on the Shift from Kampus Merdeka to Diktisaintek Berdampak - Fitriana, Septi; Hendrilia, Yudi; Judijanto, Loso; Sulaeman, Sulaeman; Anwar, Rosyida Nurul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to understand the complexity of higher education policy transformation in Indonesia by comparing two major policy approaches: Kampus Merdeka and Diktisaintek Berdampak. Using a descriptive qualitative approach and the method of literature review, this research analyzes various secondary sources such as official policy documents, scholarly journals, academic books, and research reports. The findings indicate that Kampus Merdeka focuses on learning flexibility, institutional autonomy, and strengthening student engagement with the professional world and society, although its implementation still faces infrastructure challenges and disparities between institutions. Meanwhile, Diktisaintek Berdampak emphasizes research downstreaming, innovation commercialization, and the active role of higher education in the development of a knowledge-based economy. This shift reflects a paradigmatic change from academic autonomy toward a strategic and applicative impact orientation. In conclusion, both policies need to be synergized within an inclusive, adaptive, and collaborative higher education ecosystem to produce high-quality and competitive graduates while contributing meaningfully to national development.